Cardiovascular risk scoring and magnetic resonance imaging detected subclinical cerebrovascular disease. (30th September 2019) - Anand, Sonia S; Tu, Jack V; Desai, Dipika; Awadalla, Phillip; Robson, Paula; Jacquemont, Sébastien; Dummer, Trevor; Le, Nhu; Parker, Louise; Poirier, Paul; Teo, Koon; Lear, Scott A; et al.
Abstract: Aims : Cardiovascular risk factors are used for risk stratification in primary prevention. We sought to determine if simple cardiac risk scores are associated with magnetic resonance imaging (MRI)-detected subclinical cerebrovascular disease including carotid wall volume (CWV), carotid intraplaque haemorrhage (IPH), and silent brain infarction (SBI). Methods and results: A total of 7594 adults with no history of cardiovascular disease (CVD) underwent risk factor assessment and a non-contrast enhanced MRI of the carotid arteries and brain using a standardized protocol in a population-based cohort recruited between 2014 and 2018. The non-lab-based INTERHEART risk score (IHRS) was calculated in all participants; the Framingham Risk Score was calculated in a subset who provided blood samples ( n = 3889). The association between these risk scores and MRI measures of CWV, carotid IPH, and SBI was determined. The mean age of the cohort was 58 (8.9) years, 55% were women. Each 5-point increase (∼1 SD) in the IHRS was associated with a 9 mm 3 increase in CWV, adjusted for sex ( P < 0.0001), a 23% increase in IPH [95% confidence interval (CI) 9–38%], and a 32% (95% CI 20–45%) increase in SBI. These associations were consistent for lacunar and non-lacunar brain infarction. The Framingham Risk Score was also significantly associated with CWV, IPH, and SBI. CWV was additive and independent to the risk scores in its association with IPH and SBI. Conclusion : Simple cardiovascular risk scores are significantly associated with the presence of MRI-detected subclinical cerebrovascular disease, including CWV, IPH, and SBI in an adult population without known clinical CVD.